A method for preparing beaded barium strontium titanate nanofibers with giant dielectric low loss

The problem of insufficient dielectric constant and loss of dielectric materials in the prior art is solved by sol-gel method and electrospinning technology, and the material's huge dielectric constant and low loss characteristics are realized, and the electronic equipment's miniaturization and integration needs are met.

CN118996677BActive Publication Date: 2025-04-29SHANGHAI SECOND POLYTECHNIC UNIVERSITY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411305589.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2025-04-29
Estimated Expiration
2044-09-19

AI Technical Summary

Technical Problem

It is difficult to develop dielectric materials with high dielectric constant and low loss in the prior art, especially in meeting the needs of miniaturization and integration of modern electronic devices.

Method used

The stable barium strontium titanate precursor was prepared by sol-gel method, and the film was synthesized by electrospinning technology. Finally, after high-temperature calcination treatment, beaded barium strontium titanate nanofibers with huge dielectric low loss were obtained.

Benefits of technology

It realizes the huge dielectric constant and low loss characteristics of the material, meets the needs of miniaturization and integration of electronic equipment, and at the same time, it is simple in process, convenient in operation, cost-saving, environmentally friendly and pollution-free.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118996677B_ABST
    Figure CN118996677B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing beaded barium strontium titanate nanofibers with giant dielectric low loss, and belongs to the technical field of dielectric ceramic raw materials. The present invention uses titanium source compounds, barium source compounds and strontium source compounds as raw materials, acetic acid, acetylacetone and deionized water as solvents, dissolves the raw materials in the solvent, adds a viscosity enhancer to obtain a barium strontium titanate spinning solution, and calcines the product obtained after spinning to obtain beaded barium strontium titanate nanofibers with giant dielectric low loss. The prepared barium strontium titanate nanofibers can meet the needs of miniaturization and integration of various electronic devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of dielectric ceramic raw materials, and in particular relates to a method for preparing beaded barium strontium titanate nanofibers with giant dielectric low loss. Background Art

[0002] With the rapid development of communication technology, high-performance computing, 5G mobile communication technology, artificial intelligence and electronic automobile fields have put forward miniaturization and multifunctional requirements for microwave electronic components, and these components need to have high performance and integration capabilities. Ferroelectric materials have shown broad development prospects in the preparation of key components in the communication field, such as phase shifters, oscillators and modulators. In particular, microwave tuning devices made of ferroelectric material barium strontium titanate (BST) ceramics are very suitable for use in highly integrated circuits due to their many advantages such as fast tuning response speed, large power capacity, wide operating temperature range, small size, low power consumption, low DC drive voltage and environmental friendliness. The development of phase shifters made of ferroelectric materials is an inevitable trend to promote the development of phase shifters towards high frequency, miniaturization and low cost.

[0003] In this context, the development of capacitors has gradually tended towards high energy storage, miniaturization, light weight, low cost and high reliability. This trend has put forward higher and higher requirements on the dielectric properties of dielectric materials. High energy storage density capacitors can be used as miniaturized power sources for electronic devices due to their advantages such as fast charging and discharging speed, anti-cycle aging, and stable performance. In order to achieve this goal, it is necessary to conduct in-depth research on high energy storage density dielectric materials, especially to improve their dielectric constant and breakdown strength, in order to obtain capacitors that are both small and have high energy storage density to meet the stringent requirements of modern electronic devices. Summary of the invention

[0004] In view of the above technical problems, the present invention proposes a method for preparing beaded barium strontium titanate nanofibers with giant dielectric low loss.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] A method for preparing beaded barium strontium titanate nanofibers with giant dielectric low loss comprises the following steps:

[0007] A barium source compound and a strontium source compound are added to acetic acid and deionized water, and a spinning solution A is obtained under heating and stirring in an oil bath; a titanium source compound is added to acetylacetone and stirred to obtain a spinning solution B; the spinning solution A and the spinning solution B are mixed, and a thickener is added, and stirred to obtain a barium strontium titanate spinning solution; the barium strontium titanate spinning solution is placed in an electrostatic spinning machine for spinning, and the obtained film is calcined to obtain beaded barium strontium titanate nanofibers with giant dielectric low loss.

[0008] Furthermore, the molar ratio of the titanium source compound, the barium source compound and the strontium source compound is 10:(1-9):(9-1).

[0009] Further, the titanium source compound is one or more of tetrabutyl titanate, isobutyl titanate, tetraethyl titanate and polybutyl titanate;

[0010] The barium source compound is one or more of barium acetate, barium sulfate, barium phosphate, barium oxalate, barium perchlorate and barium metaphosphate;

[0011] The strontium source compound is one or more of strontium acetate, strontium sulfate, strontium oxalate, strontium nitrate, strontium oxide, strontium tetraborate, strontium carbonate and strontium manganate.

[0012] Furthermore, the usage ratio of the acetic acid, acetylacetone and deionized water is 20 ml: 1 g: 1 g.

[0013] Furthermore, the tackifier is one or more of polystyrene, polyvinylidene fluoride, polyethylene, polyethylene glycol, polyvinyl pyrrolidone, polyvinyl alcohol and polylactic acid.

[0014] Furthermore, the amount of the viscosity enhancer used is 5-15wt% of the total mass of the titanium source compound, the barium source compound and the strontium source compound.

[0015] Furthermore, the spinning parameters are: temperature 10-50°C, distance between needle and receiver 8-30cm, voltage 15-30kV, rate 0.1-3mL / h, humidity 20-60%, stirring time 3-12h.

[0016] Furthermore, the calcination treatment refers to treatment at 900-1300° C. in air for 2-4 hours.

[0017] The invention also provides a beaded barium strontium titanate nanofiber prepared by the preparation method.

[0018] The invention also provides an application of the beaded barium strontium titanate nanofiber in preparing capacitor materials.

[0019] Compared with the prior art, the present invention has the following advantages and technical effects:

[0020] The present invention uses a sol-gel method to prepare a stable barium strontium titanate precursor, then directly synthesizes a thin film under electrostatic spinning technology, and finally removes impurities such as a tackifier through high-temperature calcination to obtain a target product. The prepared barium strontium titanate nanofiber has a uniform aspect ratio and neatly arranged beads. It can meet the needs of miniaturization and integration of various electronic devices. As an electronic functional ceramic material with unique properties, barium strontium titanate nanofiber has broad application prospects in the fields of high energy storage, dielectric capacitors, microwave phase shifters, etc.

[0021] The method has the advantages of simple process, convenient operation and easy control, and can also save costs and protect the environment from pollution. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0023] Figure 1 is the X-ray diffraction (XRD) pattern of the sample in Example 1;

[0024] Figure 2 is a scanning electron microscope (SEM) image of the sample of Example 1;

[0025] Figure 3 It is the energy spectrum analysis (EDX) diagram of the sample in Example 1;

[0026] Figure 4 The dielectric constant diagram of the samples of Examples 1-5;

[0027] Figure 5 The dielectric loss diagram of the samples of Examples 1-5;

[0028] Figure 6 The dielectric constant diagram of the samples of Comparative Example 3-4;

[0029] Figure 7 This is the dielectric loss diagram of the samples of Comparative Example 3-4. DETAILED DESCRIPTION

[0030] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0031] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0032] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0033] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0034] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0035] The present invention has developed a simple, efficient, easy-to-operate and control method for high dielectric constants, and produced a new type of structural nanofiber. The method is used to obtain beaded barium strontium titanate nanofibers with uniform aspect ratio and neatly arranged beads. The beads and fiber parts in the beaded nanofibers form a unique micro-nano composite structure. This structure provides more interfaces and defects. At the interface between the beads and the fibers, there is charge accumulation and redistribution. This interface effect enhances the dielectric constant and dielectric loss of the material, thereby optimizing the dielectric properties of the material. Achieving a giant dielectric constant has broad application prospects, a simple preparation process, and a short cycle. The specific technical solution is as follows:

[0036] A method for preparing beaded barium strontium titanate nanofibers with giant dielectric low loss comprises the following steps:

[0037] A barium source compound and a strontium source compound are added to acetic acid and deionized water, and a spinning solution A is obtained under heating and stirring in an oil bath; a titanium source compound is added to acetylacetone and stirred to obtain a spinning solution B; the spinning solution A is mixed with the spinning solution B, and a thickener is added to obtain a barium strontium titanate spinning solution after stirring the obtained mixed solution; the barium strontium titanate spinning solution is placed in an electrostatic spinning machine for spinning, and the obtained film is calcined to obtain beaded barium strontium titanate nanofibers with giant dielectric low loss.

[0038] In the following preferred embodiments of the present invention, the molar ratio of the titanium source compound, the barium source compound and the strontium source compound is 10:(1-9):(9-1), wherein the total molar amount of the barium source compound and the strontium source compound is the same as the molar amount of the titanium source compound.

[0039] In the following preferred embodiments of the present invention, the titanium source compound is one or more of tetrabutyl titanate, isobutyl titanate, tetraethyl titanate and polybutyl titanate, preferably tetrabutyl titanate.

[0040] In the following preferred embodiments of the present invention, the barium source compound is one or more of barium acetate, barium sulfate, barium phosphate, barium oxalate, barium perchlorate and barium metaphosphate, preferably barium acetate.

[0041] In the following preferred embodiments of the present invention, the strontium source compound is one or more of strontium acetate, strontium sulfate, strontium oxalate, strontium nitrate, strontium oxide, strontium tetraborate, strontium carbonate and strontium manganate, preferably strontium acetate.

[0042] In the following preferred embodiments of the present invention, the usage ratio of acetic acid, acetylacetone and deionized water is 20ml: 1g: 1g. In the present invention, acetic acid is used as a buffer solvent, and the purpose of acetylacetone and deionized water is to improve the stability of the solution and prevent the solution from crystallizing.

[0043] In the following preferred embodiments of the present invention, the parameters of the oil bath heating and stirring are: temperature 50-120° C., time 3-12 h, and stirring speed 300-1000 rpm.

[0044] In the following preferred embodiments of the present invention, the tackifier is one or more of polystyrene, polyvinylidene fluoride, polyethylene, polyethylene glycol, polyvinyl pyrrolidone, polyvinyl alcohol and polylactic acid, preferably polyvinyl pyrrolidone.

[0045] In the following preferred embodiments of the present invention, the amount of the viscosity enhancer used is 5-15 wt %, preferably 10-14 wt %, of the total mass of the titanium source compound, the barium source compound and the strontium source compound.

[0046] In the following preferred embodiments of the present invention, the parameters in the spinning process are: temperature 10-50°C, preferably 10°C; distance 8-30cm, such as 8cm, 20cm, 25cm, 30cm; voltage 15-30kV, such as 15kV, 20kV, 25kV, 30kV; rate 0.1-3mL / h, such as 0.2mL / h, 1mL / h, 1.5mL / h, 2.5mL / h, 3mL / h; humidity 20-60%, preferably 50%; stirring time 3-12h, preferably 3h.

[0047] In the following preferred embodiments of the present invention, the calcination treatment refers to treatment at 900-1300° C. in air for 2-4 hours.

[0048] The beaded barium strontium titanate nanofibers can be prepared by the above preparation method.

[0049] The beaded barium strontium titanate nanofiber is used in preparing capacitor materials.

[0050] The "room temperature" in the present invention refers to 20-30°C unless otherwise specified.

[0051] The raw materials used in the present invention are all purchased from the market. The barium acetate, strontium acetate, acetic acid, acetylacetone, and tetrabutyl titanate used in the examples are purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. The morphology of the fiber film after spinning of the present invention is observed using a transmission electron microscope (JEM 2100F, JEOL, Japan). The crystal structure and phase analysis of BST are studied using an X-ray diffractometer (XRD, Bruker, Germany). The dielectric constant and dielectric loss are measured using a precision LCR meter (Agilent E4980A, USA).

[0052] The technical solution of the present invention is further illustrated by the following embodiments.

[0053] Example 1

[0054] A method for preparing beaded barium strontium titanate nanofibers with giant dielectric low loss, the steps are as follows:

[0055] (1) Preparation of barium strontium titanate spinning solution (the molar ratio of titanium source compound, barium source compound and strontium source compound is 10:1:9)

[0056] 0.532 g of barium acetate (0.1 mol) and 3.852 g of strontium acetate (0.9 mol) were added to 20 mL of acetic acid and 1 g of deionized water and stirred for 12 h in an oil bath at 120° C. and a stirring speed of 300 rpm to obtain a spinning solution A; 7.0892 g of tetrabutyl titanate (1 mol) and 1 g of acetylacetone were mixed and stirred for 1 h to obtain a spinning solution B;

[0057] The spinning solution A and the spinning solution B were fully mixed, 0.8 g of polyvinyl pyrrolidone (the added amount was 11.0 wt% of the total mass of the titanium source compound, the barium source compound and the strontium source compound) was added, and stirred for 4 hours to obtain the barium strontium titanate spinning solution.

[0058] (2) Preparation of barium strontium titanate nanofibers

[0059] After ultrasonic dispersion of the barium strontium titanate spinning solution for 1.5 hours, pour it into a liquid tube and place it on a syringe pump. The voltage is applied by a high-voltage power supply, the liquid supply device adjusts the spinning rate, and the polymer fiber film is collected by a sample collection device. The distance between the needle and the receiver is 25 cm, the spinning rate of the spinning solution is 1.5 mL / h, the spinning voltage is 25 kV, the temperature is 10 ° C, the humidity is 20%, the stirring time is 12 hours, and the sample obtained after spinning is dried, and then the dried sample is calcined at 900 ° C for 3 hours to obtain a sample of barium strontium titanate nanofibers. The sample is characterized and tested by XRD, SEM, and LCR instruments.

[0060] Figure 1 is the X-ray diffraction pattern of the sample prepared in Example 1. Figure 1 It can be seen that the sample presents an obvious crystalline structure without obvious impurity peaks. In addition, the obvious peaks of the sample in the figure are (100), (110), (111), (200), (210), (211), (220), (221), and (310), indicating that the sample is a perovskite structure and the obtained sample is composed of barium titanate and strontium titanate.

[0061] Figure 2 This is a scanning electron microscope image of the sample prepared in Example 1. Figure 2 It can be seen that the beaded nanofibers in the sample grew well and were uniform in size, and the impurities were completely removed by heat treatment.

[0062] Figure 3 This is the energy spectrum analysis diagram of the sample prepared in Example 1. Figure 3 It can be seen that all elements are evenly dispersed without segregation, which proves the formation of barium strontium titanate.

[0063] Figure 4 is the dielectric constant of the sample prepared in Example 1, Figure 4 It can be seen that at 100 Hz, the dielectric constant reaches a maximum of 7195, indicating that the sample has the characteristics of giant dielectric.

[0064] Figure 5 The dielectric loss of the sample prepared in Example 1 is Figure 5 It can be seen that the highest dielectric loss is 0.211, which indicates that the sample has low loss characteristics.

[0065] Example 2

[0066] A method for preparing beaded barium strontium titanate nanofibers with giant dielectric low loss, the steps are as follows:

[0067] (1) Preparation of barium strontium titanate spinning solution (the molar ratio of titanium source compound, barium source compound and strontium source compound is 10:3:7)

[0068] 1.596 g of barium acetate (0.3 mol) and 2.996 g of strontium acetate (0.7 mol) were added to 20 mL of acetic acid and 1 g of deionized water and stirred for 5 h in a 70°C oil bath and a stirring speed of 1000 rpm to obtain spinning solution A; 7.09 g of tetrabutyl titanate (1 mol) and 1 g of acetylacetone were mixed and stirred for 1 h to obtain spinning solution B;

[0069] The spinning solution A and the spinning solution B were fully mixed, 0.8 g of polyvinyl pyrrolidone (the added amount was 10.8 wt% of the total mass of the titanium source compound, the barium source compound and the strontium source compound) was added, and stirred for 5 hours to obtain the barium strontium titanate spinning solution.

[0070] (2) Preparation of barium strontium titanate nanofibers

[0071] After ultrasonic dispersion of the barium strontium titanate spinning solution for 1.5 hours, pour it into a liquid tube and place it on a syringe pump. The voltage is applied by a high-voltage power supply, the liquid supply device adjusts the spinning rate, and the polymer fiber film is collected by a sample collection device. The distance between the needle and the receiver is 25 cm, the spinning rate of the spinning solution is 1 mL / h, the spinning voltage is 15 kV, the temperature is 50 ° C, the humidity is 60%, the stirring time is 3 hours, and the sample obtained after spinning is dried, and then the dried sample is calcined at 1200 ° C for 2 hours to obtain a sample of barium strontium titanate nanofibers. The sample is characterized and tested by XRD, SEM, and LCR.

[0072] The X-ray diffraction of the sample prepared in this example shows that the obtained sample has a clear crystalline structure, no obvious impurity peaks appear, and the sample is a perovskite structure. Scanning electron microscopy shows that the beaded nanofibers in the sample grow well and are uniform in size, and impurities are completely removed by heat treatment. Energy spectrum analysis shows that all elements are evenly dispersed without segregation. These results prove the formation of barium strontium titanate. The dielectric constant shows (see Figure 4 ), at 100Hz, the dielectric constant reaches a maximum of 21852, which shows that the sample has the characteristics of giant dielectric. The dielectric loss is shown in (see Figure 5 ), the highest dielectric loss is 0.490, which indicates that the sample has low loss characteristics.

[0073] Example 3

[0074] A method for preparing beaded barium strontium titanate nanofibers with giant dielectric low loss, the steps are as follows:

[0075] (1) Barium strontium titanate spinning solution (the molar ratio of titanium source compound, barium source compound and strontium source compound is 10:7:3)

[0076] 3.724 g of barium acetate (0.7 mol) and 1.284 g of strontium acetate (0.3 mol) were added to 20 mL of acetic acid and 1 g of deionized water and stirred for 5 h in an oil bath at 80° C. and a stirring speed of 600 rpm to obtain a spinning solution A; 7.0892 g of tetrabutyl titanate (1 mol) and 1 g of acetylacetone were mixed and stirred for 1 h to obtain a spinning solution B;

[0077] The spinning solution A and the spinning solution B were fully mixed, 1 g of polyvinyl pyrrolidone (the added amount was 13.9 wt% of the total mass of the titanium source compound, the barium source compound and the strontium source compound) was added, and stirred for 5 h to obtain the barium strontium titanate spinning solution.

[0078] (2) Preparation of barium strontium titanate nanofibers

[0079] After ultrasonic dispersion of the barium strontium titanate spinning solution for 1.5 hours, pour it into a liquid tube and place it on a syringe pump. The voltage is applied by a high-voltage power supply, the liquid supply device adjusts the spinning rate, and the polymer fiber film is collected by a sample collection device. The distance between the needle and the receiver is 20 cm, the spinning rate of the spinning solution is 2.5 mL / h, the spinning voltage is 30 kV, the temperature is 30 ° C, the humidity is 30%, the stirring time is 5 hours, and the obtained sample is dried after the spinning is completed. Then, the dried sample is calcined at 1300 ° C for 2 hours to obtain a sample of barium strontium titanate nanofibers. The sample is characterized and tested by XRD, SEM, and LCR instruments.

[0080] The X-ray diffraction of the sample prepared in this example shows that the obtained sample has a clear crystalline structure, no obvious impurity peaks appear, and the sample is a perovskite structure. Scanning electron microscopy shows that the beaded nanofibers in the sample grow well and are uniform in size, and impurities are completely removed by heat treatment. Energy spectrum analysis shows that all elements are evenly dispersed without segregation. These results prove the formation of barium strontium titanate. The dielectric constant shows (see Figure 4 ), at 100Hz, the dielectric constant reaches a maximum of 24372, which shows that the sample has the characteristics of giant dielectric. The dielectric loss is shown in (see Figure 5 ), the highest dielectric loss is 0.169, which indicates that the sample has low loss characteristics.

[0081] Example 4

[0082] A method for preparing beaded barium strontium titanate nanofibers with giant dielectric low loss, the steps are as follows:

[0083] (1) Barium strontium titanate spinning solution (the molar ratio of the titanium source compound, the barium source compound and the strontium source compound is 10:5:5)

[0084] 2.66 g of barium acetate (0.5 mol) and 2.14 g of strontium acetate (0.5 mol) were added to 20 mL of acetic acid and 1 g of deionized water and stirred for 10 h in an oil bath at 70° C. and a stirring speed of 400 rpm to obtain a spinning solution A; 6.4 g of tetrabutyl titanate (1 mol) and 1 g of acetylacetone were mixed and stirred for 1 h to obtain a spinning solution B;

[0085] The spinning solution A and the spinning solution B were fully mixed, 0.8 g of polyvinyl pyrrolidone (the added amount was 11.0 wt% of the total mass of the titanium source compound, the barium source compound and the strontium source compound) was added, and stirred for 5 hours to obtain the barium strontium titanate spinning solution.

[0086] (2) Preparation of barium strontium titanate nanofibers

[0087] After ultrasonic dispersion of the barium strontium titanate spinning solution for 1.5 hours, pour it into a liquid tube and place it on a syringe pump. The voltage is applied by a high-voltage power supply, the liquid supply device adjusts the spinning rate, and the polymer fiber film is collected by a sample collection device. The distance between the needle and the receiver is 30 cm, the spinning rate of the spinning solution is 3 mL / h, the spinning voltage is 25 kV, the temperature is 10 ° C, the humidity is 50%, the stirring time is 10 hours, and the obtained sample is dried after the spinning is completed. Then, the dried sample is calcined at 1300 ° C for 3 hours to obtain a sample of barium strontium titanate nanofibers. The sample is characterized and tested by XRD, SEM, and LCR instruments.

[0088] The X-ray diffraction of the sample prepared in this example shows that the obtained sample has a clear crystalline structure, no obvious impurity peaks appear, and the sample is a perovskite structure. Scanning electron microscopy shows that the beaded nanofibers in the sample grow well and are uniform in size, and impurities are completely removed by heat treatment. Energy spectrum analysis shows that all elements are evenly dispersed without segregation. These results prove the formation of barium strontium titanate. The dielectric constant shows (see Figure 4 ), at 100Hz, the dielectric constant reaches a maximum of 9289, which shows that the sample has giant dielectric properties. The dielectric loss is shown in (see Figure 5 ), the highest dielectric loss is 0.195, which indicates that the sample has low loss characteristics.

[0089] Example 5

[0090] A method for preparing beaded barium strontium titanate nanofibers with giant dielectric low loss, the steps are as follows:

[0091] (1) Barium strontium titanate spinning solution (the molar ratio of titanium source compound, barium source compound and strontium source compound is 10:9:1)

[0092] 4.788 g of barium acetate (0.9 mol) and 0.428 g of strontium acetate (0.1 mol) were added to 20 mL of acetic acid and 1 g of deionized water under heating conditions of 100° C. oil bath and stirring speed of 800 rpm, and stirred for 6 h to obtain spinning solution A; 7.089 g of tetrabutyl titanate (1 mol) and 0.5 g of acetylacetone were mixed and stirred for 1 h to obtain spinning solution B;

[0093] The spinning solution A and the spinning solution B were fully mixed, 0.8 g of polyvinyl pyrrolidone (the added amount was 10.7 wt% of the total mass of the titanium source compound, the barium source compound and the strontium source compound) was added, and stirred for 5 hours to obtain the barium strontium titanate spinning solution.

[0094] (2) Preparation of barium strontium titanate nanofibers

[0095] After ultrasonic dispersion of the barium strontium titanate spinning solution for 1.5 hours, pour it into a liquid tube and place it on a syringe pump. The voltage is applied by a high-voltage power supply, the liquid supply device adjusts the spinning rate, and the sample collection device collects the polymer fiber film. The distance between the needle and the receiver is 8 cm, the spinning rate of the spinning solution is 0.2 mL / h, the spinning voltage is 20 kV, the temperature is 40 ° C, the humidity is 40%, the stirring time is 6 hours, and the obtained sample is dried after the spinning is completed. Then, the dried sample is calcined at 1100 ° C for 4 hours to obtain a sample of barium strontium titanate nanofibers. The sample is characterized and tested by XRD, SEM, and LCR.

[0096] The X-ray diffraction of the sample prepared in this example shows that the obtained sample has a clear crystalline structure, no obvious impurity peaks appear, and the sample is a perovskite structure. Scanning electron microscopy shows that the beaded nanofibers in the sample grow well and are uniform in size, and impurities are completely removed by heat treatment. Energy spectrum analysis shows that all elements are evenly dispersed without segregation. These results prove the formation of barium strontium titanate. The dielectric constant shows (see Figure 4 ), at 100Hz, the dielectric constant reaches a maximum of 8503, which shows that the sample has the characteristics of giant dielectric. The dielectric loss is shown in (see Figure 5 ), the highest dielectric loss is 0.414, which indicates that the sample has the characteristics of low loss.

[0097] Comparative Example 1

[0098] The technical solution of the publication number CN108530056A and the title "A giant dielectric low-loss barium strontium titanate ceramic and its preparation method":

[0099] (1) Weigh 0.0746 g of SrCO3, 0.897 g of BaCO3 and 0.4034 g of TiO2, ball-mill the raw materials for 16 h at a mass ratio of raw material: agate ball mill: anhydrous ethanol = 1:1.2:1.2, and dry to obtain a mixed powder;

[0100] (2) keeping the mixed powder obtained in step (1) at 1100° C. for 4 h to obtain barium strontium titanate powder;

[0101] (3) According to the mass ratio Ba 1-x Sr x TiO3 powder: agate ball mill: anhydrous ethanol = 1: 1.2: 1.2. The barium strontium titanate powder is ball-milled for 16 hours, and the ball-milled slurry is passed through a 120-mesh screen and dried in an air atmosphere; then 0.8 g of a 4 wt% polyvinyl alcohol aqueous solution is added to 1.5 g of the dried powder as a binder to form granules, and the granulated powder is passed through a 40-mesh screen and maintained at a pressure of 20 MPa for 5 minutes, and then subjected to cold isostatic pressing at a pressure of 190 MPa for 2 minutes to obtain a ceramic body;

[0102] (4) The ceramic body obtained in step (3) was slowly heated to 600°C in air at a heating rate of 2°C / min, kept at 600°C for 3 hours, and naturally cooled to room temperature. After the binder was removed, it was sintered at 1300°C for 5 hours to produce Ba 0.7 Sr 0.3 TiO3 ceramic samples.

[0103] Comparative Example 2

[0104] The technical solution with publication number CN118026669 and titled "Method for regulating oxygen partial pressure and performance during sintering of barium strontium titanate using coconut shell":

[0105] Step 1: Coconut shell selection and cleaning; select old coconut shells with thick and hard shells, clean them, remove the fibers on them until the surface is smooth, and use a high-temperature blast drying oven set at 120℃ to dehydrate and dry for 2 hours;

[0106] Step 2: Coconut shell crushing and high-temperature carbonization: Coconut shell crushes the dried coconut shell into small pieces, puts them into a crucible, and performs high-temperature carbonization in a muffle furnace, with a maximum temperature of 900°C, and is kept warm for 2 hours. The maximum heating rate is 5°C / min. The specific process is: 20°C-36min-200°C-80min-600°C-60min-900°C-120min-900°C-60min-500°C-cooling with the furnace;

[0107] Step 3: Grind and sieve the coconut shell carbonized; take out the coconut shell charcoal after high temperature carbonization, grind it, and sieve it with a 150-mesh sieve to ensure that the size of the coconut shell charcoal is small enough;

[0108] Step 4: Mix and grind the coconut shell charcoal and barium titanate powder in proportion; weigh the coconut shell charcoal and barium titanate powder in a mass ratio of 2%, 4%, and 6%, respectively, and grind to fully mix the coconut shell charcoal and barium titanate powder;

[0109] Step 5: tabletting the mixed powder; PVA solution is added to the mixed powder as a binder, and the powder is tabletted after sufficient grinding to obtain a green blank in which coconut shell charcoal and barium titanate are fully mixed, and each green blank weighs between 0.36 and 0.37 g;

[0110] Step 6: Sintering: Put the pressed green blank into a muffle furnace and sinter it at high temperature, with a maximum temperature of 1275°C, keep warm for 2 hours, and a maximum heating rate of 5°C / min. The specific process is: 20°C-30min-200°C-80min-600°C-30min-600°C-125min-1225°C-50min-1275°C-120min-1275°C-60min-500°C-cooling with the furnace;

[0111] Step 7: Conduct various performance tests on the sintered coconut shell carbon doped barium titanate ceramics.

[0112] Comparative Example 3

[0113] The same as Example 3, except that the parameters in the spinning process are: temperature 30°C, distance 20cm, voltage 30kV, speed 5mL / h, humidity 30%, stirring time 5h. The sample barium strontium titanate nanofibers were obtained. Due to the excessive spinning speed, the nanofibers were relatively thick and short, which affected the dielectric properties, resulting in a decrease in the dielectric constant and an increase in the dielectric loss. The dielectric constant is shown in (see Figure 6 ), at 100Hz, the dielectric constant reaches a maximum of 4312. The dielectric loss is shown in (see Figure 7 ), the maximum dielectric loss is 0.5141.

[0114] Comparative Example 4

[0115] Same as Example 3, except that the calcination temperature was 1500°C and the calcination time was 4 hours. The sample barium strontium titanate nanofiber was obtained. Due to the high sintering temperature, the structure crystallization was affected, resulting in a decrease in the dielectric constant and an increase in the dielectric loss. The dielectric constant is shown in (see Figure 6 ), at 100Hz, the dielectric constant reaches a maximum of 2460. The dielectric loss is shown as shown (see Figure 7 ), the maximum dielectric loss is 0.4966.

[0116] The thermal conductivity and dielectric properties of the samples prepared in Examples 1-9 and Comparative Examples 1-7 were measured at room temperature. The results are shown in Tables 1 and Figure 4 , Figure 5 .

[0117] Table 1

[0118]

[0119]

[0120] As can be seen from Table 1, the samples prepared by the preparation methods of Examples 1-5 have high dielectric constants and low dielectric losses. The dielectric loss of Example 1 is slightly higher because the high strontium content in the formed barium strontium titanate will increase the dielectric loss; the high dielectric loss of Example 5 is because the low strontium content will also increase the dielectric loss; the dielectric constant obtained in Example 3 is the highest and the dielectric loss is the lowest. Compared with Comparative Example 1, the dielectric constant of Example 3 is much higher than that of Comparative Example 1 and Comparative Example 2. This is mainly because the sample prepared by the method of Example 3 of the present invention can make the beaded nanofibers more crystallinity, greatly improve the dielectric constant of the material, and reduce the dielectric loss due to the special structure of the beaded nanofibers.

[0121] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A method for preparing beaded barium strontium titanate nanofibers with giant dielectric low loss, characterized in that: The following steps are involved: A barium source compound and a strontium source compound are added to acetic acid and deionized water, and a spinning solution A is obtained under heating and stirring in an oil bath; a titanium source compound is added to acetylacetone and stirred to obtain a spinning solution B; the spinning solution A and the spinning solution B are mixed, a viscosity enhancer is added, and the mixture is stirred to obtain a barium strontium titanate spinning solution; the barium strontium titanate spinning solution is placed in an electrostatic spinning machine for spinning, and the obtained film is calcined to obtain beaded barium strontium titanate nanofibers with giant dielectric low loss; The spinning rate during the spinning process is 1-3 mL / h; The calcination temperature is 900-1300°C; The calcination time is 2-4 hours.

2. The method for preparing beaded barium strontium titanate nanofibers with giant dielectric low loss according to claim 1, characterized in that: The molar ratio of the titanium source compound, the barium source compound and the strontium source compound is 10:(1-9):(9-1).

3. The method for preparing beaded barium strontium titanate nanofibers with giant dielectric low loss according to claim 2, characterized in that: The titanium source compound is one or more of tetrabutyl titanate, isobutyl titanate, tetraethyl titanate and polybutyl titanate; The barium source compound is one or more of barium acetate, barium sulfate, barium phosphate, barium oxalate, barium perchlorate and barium metaphosphate; The strontium source compound is one or more of strontium acetate, strontium sulfate, strontium oxalate, strontium nitrate, strontium oxide, strontium tetraborate, strontium carbonate and strontium manganate.

4. The method for preparing beaded barium strontium titanate nanofibers with giant dielectric low loss according to claim 1, characterized in that: The usage ratio of the acetic acid, acetylacetone and deionized water is 20ml:1g:1g.

5. The method for preparing beaded barium strontium titanate nanofibers with giant dielectric low loss according to claim 1, characterized in that: The tackifier is one or more of polystyrene, polyvinylidene fluoride, polyethylene, polyethylene glycol, polyvinyl pyrrolidone, polyvinyl alcohol and polylactic acid.

6. The method for preparing beaded barium strontium titanate nanofibers with giant dielectric low loss according to claim 1, characterized in that: The amount of the viscosity enhancer used is 5-15 wt % of the total weight of the titanium source compound, the barium source compound and the strontium source compound.

7. The method for preparing beaded barium strontium titanate nanofibers with giant dielectric low loss according to claim 1, characterized in that: The spinning parameters are: temperature 10-50° C., distance between needle and receiver 8-30 cm, voltage 15-30 kV, humidity 20-60%, stirring time 3-12 h.

8. Beaded barium strontium titanate nanofibers prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the beaded barium strontium titanate nanofibers as claimed in claim 8 in preparing capacitor materials.

Citation Information

Patent Citations

  • Giant dielectric low-loss barium strontium titanate ceramic and preparation method thereof

    CN108530056A

  • Method for synthesis of strontium-barium titanate nanotubes

    CN103526337A

  • Superfine barium strontium titanate nanofiber-based flexible film and preparation method thereof

    CN113026146A